2011
DOI: 10.1007/s10461-011-0052-6
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of an HIV Risk Reduction Intervention for Hispanic Women

Abstract: Culturally-specific HIV risk reduction interventions for Hispanic women are needed. SEPA (Salud/Health, Educación/Education, Promoción/Promotion, y/ and Autocuidado/Self-care) is a culturally-specific and theoretically-based group intervention for Hispanic women. The SEPA intervention consists of five sessions covering STI and HIV prevention; communication, condom negotiation and condom use; and violence prevention. A randomized trial tested the efficacy of SEPA with 548 adult U.S. Hispanic women (SEPA n = 274… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
129
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(148 citation statements)
references
References 25 publications
13
129
1
5
Order By: Relevance
“…The SHH also asked participants to report their HIV status as well as information on diagnosed STIs as reported by participants. The SHH has been used in previous studies with Hispanic women (Gonzalez-Guarda et al, 2011; Peragallo et al, 2005; Peragallo et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…The SHH also asked participants to report their HIV status as well as information on diagnosed STIs as reported by participants. The SHH has been used in previous studies with Hispanic women (Gonzalez-Guarda et al, 2011; Peragallo et al, 2005; Peragallo et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…18 The lack of significant differences in IPV outcomes at the 6-month follow-up between Computerized WORTH and control conditions is consistent with some IPV intervention studies, which found stronger effects at 12 months than at 6 months postintervention. 24,39 The delayed effect of WORTH on reducing IPV suggests that it may take more time for women on average to successfully implement their safety planning skills to avoid risks for IPV, access services, and leave abusive partners.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, only 2 integrated interventions have been found to be efficacious in reducing IPV among women. 24,25 To date, no integrated interventions have emerged that have shown efficacy in reducing the syndemic risk of sexual IPV (i.e., forced sex by an intimate partner) among substance-using women.…”
mentioning
confidence: 99%
“…To test our hypothesis we designed a questionnaire that incorporated both previous psychometrically validated questions from several studies [14,16,19,22] and questions designed to gather information about our particular population's demographics and medical history. The questionnaire consisted of five sections: Demographics, Obstetrical History, Sexual History, Sexual Knowledge, and Condom Negotiation Strategies with a total of 31 questions.…”
Section: Methodsmentioning
confidence: 99%
“…A recent survey found that only 21.8% of women used a condom during their last sexual encounter [10]. Several studies have identified barriers to consistent and correct condom use, specifically partner preference [11], physical and emotional violence, [1,12] limited sexual knowledge,13,14 and weak/limited negotiation strategies [13][14][15]. Proven motivators of condom use among females include gender empowerment, [16,17] HIV and STI knowledge [13][14][15], and well developed communication skills and negotiation strategies [13,14].…”
mentioning
confidence: 99%